2015
DOI: 10.1176/appi.ps.201300551
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Mental Health Care for Female Veterans

Abstract: Objective-Mental health services for women vary widely across the Veterans Health Administration (VHA) system, without consensus on the need for, or organization of, specialized services for women. Understanding women's needs and priorities is essential to guide the implementation of patient-centered behavioral health services.Methods-In a cross-sectional, multisite survey of female veterans using primary care, potential stakeholders were identified for VHA mental health services by assessing perceived or obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…For example, behavioral health interventions (including promoting physical activity and weight loss, smoking cessation, and mental health services) may be adapted to best address women's needs and preferences (e.g., offering access to women-only programs, same-gender providers, gender-specific treatment guidelines, and gender-sensitive care; see deKleijn et al, 2015). Studies on gender-specific behavioral health services and preferences have shown that women veterans reported strong preferences for having designated women's services for PTSD, depression, and coping with chronic medical conditions (Kimerling et al, 2015), as well as weight management (Goldstein et al, 2017).…”
Section: Implications For Practice And/or Policymentioning
confidence: 99%
“…For example, behavioral health interventions (including promoting physical activity and weight loss, smoking cessation, and mental health services) may be adapted to best address women's needs and preferences (e.g., offering access to women-only programs, same-gender providers, gender-specific treatment guidelines, and gender-sensitive care; see deKleijn et al, 2015). Studies on gender-specific behavioral health services and preferences have shown that women veterans reported strong preferences for having designated women's services for PTSD, depression, and coping with chronic medical conditions (Kimerling et al, 2015), as well as weight management (Goldstein et al, 2017).…”
Section: Implications For Practice And/or Policymentioning
confidence: 99%
“…Some disparities exist for inpatient care, where women report poorer experiences as compared to men for care experiences that may be sensitive to patient activation, such as shared decision making, communication about medications, and communication of discharge information (Hausmann et al 2014). Women veterans report distinct gender-related preferences regarding mental health services (Kimerling et al 2014), such as preferences for female providers, women-only groups, or designated women’s treatment settings. These preferences vary as a function of demographic and service characteristics, the conditions being treated, and comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…15 To date, few studies have examined the impact of perceptions of mental health care on mental health utilization. Negative perceptions about the gender sensitivity of VA health care are associated with unmet need for care among women veterans.…”
mentioning
confidence: 99%